2006
DOI: 10.1111/j.1420-9101.2006.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm competition games: the risk model can generate higher sperm allocation to virgin females

Abstract: We examine the risk model in sperm competition games for cases where female fertility increases significantly with sperm numbers (sperm limitation). Without sperm competition, sperm allocation increases with sperm limitation. We define ‘average risk’ as the probability q that females in the population mate twice, and ‘perceived risk’ as the information males gain about the sperm competition probability with individual females. If males obtain no information from individual females, sperm numbers increase with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 57 publications
3
36
1
Order By: Relevance
“…It is not known how many spermatophores were passed during these observations. However, if it is assumed that longer copulation times enable males to transfer more spermatophores to females, as has been reported for some insects (Sakaluk & Eggert, 1996), then this behaviour was consistent with the risk model outlined by Ball and Parker (2007). These researchers suggested that when sperm supply is limited and female mating status is known, it is advantageous for males to allocate more sperm to virgin females in order to ensure paternity amongst future competing sperm given to that female.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is not known how many spermatophores were passed during these observations. However, if it is assumed that longer copulation times enable males to transfer more spermatophores to females, as has been reported for some insects (Sakaluk & Eggert, 1996), then this behaviour was consistent with the risk model outlined by Ball and Parker (2007). These researchers suggested that when sperm supply is limited and female mating status is known, it is advantageous for males to allocate more sperm to virgin females in order to ensure paternity amongst future competing sperm given to that female.…”
Section: Discussionsupporting
confidence: 70%
“…Relevant models of sperm competition, where sperm supply is limited, imply that male cephalopods could potentially achieve optimal fertilisation success by investing less time copulating with females that they have already mated with (Parker, 1970), with females that are holding less sperm from competing males and therefore pose less risk of sperm competition (Ball & Parker, 2007), and/or when additional factors such as male mating order might give males an inherent advantage towards successful fertilisation (Parker, 1990). Likewise, male cephalopods should be expected to invest more time and/or spermatophores with novel females and females posing a high-risk of sperm competition (Parker, 1970;1990;Parker et al, 1997;Ball & Parker, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…where N f , N m are the number of breeding females and males, respectively Ball 2005, Ball andParker 2007). Thus at the ESS, remembering that…”
Section: General Resultsmentioning
confidence: 99%
“…In contrast, as intensity increases above one competitor, resource allocation should decrease as returns diminish with more competition (Parker et al, 1996Ball and Parker, 1997). In general, the outcome of sperm competition models is dependent on the mating status of females, the probability of female remating and number of competitors, but crucially also on the quality of information that the male has about these parameters (Ball and Parker, 2007;Parker and Pizzari, 2010). A further consideration is whether the competition is a fair or loaded raffle, and if the latter, which is the favoured role (i.e.…”
Section: Introductionmentioning
confidence: 95%